Ectopic expression of a novel OsExtensin‐like gene consistently enhances plant lodging resistance by regulating cell elongation and cell wall thickening in rice. Issue 1 (15th July 2017) - Fan, Chunfen; Li, Ying; Hu, Zhen; Hu, Huizhen; Wang, Guangya; Li, Ao; Wang, Youmei; Tu, Yuanyuan; Xia, Tao; Peng, Liangcai; Feng, Shengqiu
Summary: Plant lodging resistance is an important integrative agronomic trait of grain yield and quality in crops. Although extensin proteins are tightly associated with plant cell growth and cell wall construction, little has yet been reported about their impacts on plant lodging resistance. In this study, we isolated a novel extensin‐like (OsEXTL) gene in rice, and selected transgenic rice plants that expressed OsEXTL under driven with two distinct promoters. Despite different OsEXTL expression levels, two‐promoter‐driven OsEXTL ‐transgenic plants, compared to a rice cultivar and an empty vector, exhibited significantly reduced cell elongation in stem internodes, leading to relatively shorter plant heights by 7%–10%. Meanwhile, the OsEXTL ‐transgenic plants showed remarkably thickened secondary cell walls with higher cellulose levels in the mature plants, resulting in significantly increased detectable mechanical strength (extension and pushing forces) in the mature transgenic plants. Due to reduced plant height and increased plant mechanical strength, the OsEXTL ‐transgenic plants were detected with largely enhanced lodging resistances in 3 years field experiments, compared to those of the rice cultivar ZH11. In addition, despite relatively short plant heights, the OsEXTL ‐transgenic plants maintain normal grain yields and biomass production, owing to their increased cellulose levels and thickened cell walls. Hence, this study demonstrates a largely improved lodging resistance in the OsEXTL ‐transgenic rice plants, and provides insights into novel extensin functions in plant cell growth and development, cell wall network construction and wall structural remodelling.